2013
DOI: 10.1103/physrevlett.111.200402
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Spectral Homodyne Detection: Complete Quantum Measurement of Spectral Modes of Light

Abstract: Spectral homodyne detection, a widely used technique for measuring quantum properties of light beams, cannot retrieve all the information needed to reconstruct the quantum state of spectral field modes. We show that full quantum state reconstruction can be achieved with the alternative measurement technique of resonator detection. We experimentally demonstrate this difference by engineering a quantum state with features that go undetected by homodyne detection but are clearly revealed by resonator detection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 36 publications
2
50
0
3
Order By: Relevance
“…To overcome this issue, a resonator detection method has been proposed and demonstrated in Refs. [1,32]. In our case we can exploit the error signal from the PDH stabilization to check the symmetry of the sideband state and also to measure the presence of some energy unbalance of the two sidebands, leading to non-vanishing δ ll .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this issue, a resonator detection method has been proposed and demonstrated in Refs. [1,32]. In our case we can exploit the error signal from the PDH stabilization to check the symmetry of the sideband state and also to measure the presence of some energy unbalance of the two sidebands, leading to non-vanishing δ ll .…”
mentioning
confidence: 99%
“…In order to retrieve the full information about the sidebands it has been suggested that one should spatially separate the two modes [30,31] or implement more sophisticated setups [1,32] involving resonator detection. On the other hand, it would be desirable to have schemes, which do not require structural modifications of the experimental setup.…”
mentioning
confidence: 99%
“…At the same time a single-ended cavity could be employed to rotate the squeezed quadrature angle with respect to the carrier to allow for full characterization of the squeezed field using self-homodyne detection. 20,21 While detecting the on-chip generated squeezed light will be the next step, we expect the squeezing degree to be mainly limited by optical loss due to inefficient fiber coupling. Achieving better coupling efficiencies, for instance by tuning the Gaussian mode profile given by the lensed fibers, has to be investigated as well as possible reductions of waveguide propagation loss.…”
Section: Discussionmentioning
confidence: 99%
“…In principle it is possible to reconstruct the quantum state of a two-color photon beam by spectrum analysis of the time-dependent photon intensity. It is shown in appendix C that the analysis of [23,24] carries over to the context of reducible QED.…”
Section: Fluctuations Of the Electric Field Operatormentioning
confidence: 99%